PENINGKATAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Rahayu Wibowo; A. A Sujadi; Esti Harini (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
the purpose of this study was to improve interest and mathematics achievement in cooperative students of class VII SMP Sanjaya Ngawen Gunungkidul with Jigsaw. This research was Classroom Action Research (CAR). The subjects in this study were students of class VII which was 16 students. Research findings indicate that interest and mathematics achievement. It can be shown by an increase in the average yield percentage of student learning interest. Based on the questionnaire for each cycle, in the first cycle of student interest was 65,94% and for the second cycle was 75,31%. While the average value interpretation of students mathematics learning increased from an average initial value of the average ofÂ  64,68 up to 67,18 in the first cycle and the second cycle to 75,31